Are formalin‐fixed and paraffin‐embedded tissues fit for proteomic analysis?. (10th April 2019) - Bayer, Malte; Angenendt, Linus; Schliemann, Christoph; Hartmann, Wolfgang; König, Simone
Abstract: Formalin‐fixed and paraffin‐embedded (FFPE)–tissue archives are potential treasure troves in the search for clinically interesting specimens. However, while the FFPE‐treatment provides excellent conservation of the three‐dimensional structure of the tissue and prevents degradation over decades, it also introduces numerous nonspecific and irreversible protein modifications. In this study, we have evaluated several published workflows for FFPE‐tissue by fit‐for‐purpose proteomics technologies. We demonstrate that many protein modifications and cross‐links remain after treatment and conclude that the proteomics of FFPE‐tissue is of value, but clear‐cut limitations must be kept in mind. The analysis of abundant proteins in FFPE is straightforward, but confident identification of low‐level proteins and/or biologically relevant modifications is seriously hampered by the FFPE‐treatment. Peptide assignment should only be performed on high‐quality spectra, even if this is at the cost of lower numbers of protein IDs. As Yergey and Coorssen stated in 2015: "Data quality is considered the primary criterion, and we thus emphasize that the standards of Analytical Chemistry must apply throughout any proteomic analysis."